2022
DOI: 10.3389/fped.2022.823847
|View full text |Cite
|
Sign up to set email alerts
|

Anakinra in Paediatric Rheumatology and Periodic Fever Clinics: Is the Higher Dose Safe?

Abstract: ObjectiveAnakinra has been increasingly used in off-label indications as well as dosing and mode of administration in a variety of inflammatory conditions. We aimed to review our clinical practice and compare treatment outcomes with published data.MethodsClinical data from electronic records were retrospectively reviewed for patients treated with anakinra over the past 6 years for autoinflammatory diseases (AID).ResultsFrom 47 eligible patients (27 female patients), 32 were children. Macrophage activation synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Individual patients may tolerate or respond differently to the various preparations [ 7 , 8 , 9 , 10 , 11 ]. However, certain patients may not tolerate or respond effectively to colchicine and, therefore, require alternative treatments such as IL-1 targeting agents [ 13 , 14 , 15 , 16 ]. Patients requiring biological drugs often encounter accessibility challenges, such as physicians refusing to prescribe medications due to high costs, insurance companies not approving biological medications, limited approval (only a small number of patients are allocated to receive medication), or the drugs not being available in the patient’s country of residence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual patients may tolerate or respond differently to the various preparations [ 7 , 8 , 9 , 10 , 11 ]. However, certain patients may not tolerate or respond effectively to colchicine and, therefore, require alternative treatments such as IL-1 targeting agents [ 13 , 14 , 15 , 16 ]. Patients requiring biological drugs often encounter accessibility challenges, such as physicians refusing to prescribe medications due to high costs, insurance companies not approving biological medications, limited approval (only a small number of patients are allocated to receive medication), or the drugs not being available in the patient’s country of residence.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin (IL)-1 inhibitors such as anakinra, canakinumab, and rilonacept are effective in the treatment of many different AIDs [ 6 , 7 , 8 , 9 , 10 ]. However, these biological drugs are not available in all countries, making effective disease control difficult [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Schmitz et al's study shows that the blockage of IL-1 has been associated with the reversal of acute lung injury in avian influenza [ 23 ]. Fingerhutová et al's study demonstrated that aggressive therapy of MAS using continuous IV anakinra infusions in higher doses successfully reverses the cytokine storm, especially in the pediatric population [ 24 ]. In the case of our patient, treatment with different modalities like upgrading antibiotics, two courses of corticosteroid, IVIG, and SQ with IV push of anakinra did not provide clinical improvement immediately.…”
Section: Discussionmentioning
confidence: 99%